2015
DOI: 10.1002/mrd.22488
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory fetal membrane mechanisms between biglycan and decorin in inflammation

Abstract: Preterm premature rupture of fetal membranes (PPROM) is associated with infection and is one of the most common causes of preterm birth. Abnormalities of biglycan and decorin, two extracellular matrix proteoglycans, lead to preterm birth and abnormal fetal membrane morphology and abnormal signaling in the mouse model as well as being associated with inflammatory cascades. In humans, decorin dysregulation is associated with inflammation in PPROM. We investigated biglycan and decorin’s role in inflammation in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…This elevated anticoagulant activity was attributed to a DS proteoglycan [ 131 ], later identified as DCN in the human term placenta [ 132 ]. Both of these interactions may account for proposed roles of DCN in immune signaling [ 133 , 134 ] and blocking thrombosis [ 135 ] involving several abnormal pregnancies.…”
Section: Mode Of Action Of Dcnmentioning
confidence: 99%
“…This elevated anticoagulant activity was attributed to a DS proteoglycan [ 131 ], later identified as DCN in the human term placenta [ 132 ]. Both of these interactions may account for proposed roles of DCN in immune signaling [ 133 , 134 ] and blocking thrombosis [ 135 ] involving several abnormal pregnancies.…”
Section: Mode Of Action Of Dcnmentioning
confidence: 99%
“…Skeletal manifestations are observed in mouse models in which specific SLRP genes were ablated or altered (leading to altered post-translational modifications), in some cases paralleling clinical phenotypes of human diseases, that is, in spite of compensatory expression of other members of the same sub-class of the ablated SLRP gene. 44,88,89 Many of the clinical phenotypes are associated with abnormal collagen fibril size, shape, and cross-linking. 13,30,[37][38][39][40] Though Decorin is expressed in bone, Decorin-deficient mice did not manifest any changes to bone mass or architecture.…”
Section: Animal Modelsmentioning
confidence: 99%
“…For the preanalytical and covariate studies, samples were selected from singleton pregnancies in order to assess the effects of gestational age (weeks [15][16][17][18][19][20], freezer storage (0, 6, or 12 months), and maternal race (African American or Non-African American) on biglycan and decorin serum values. Serum samples from nonpregnant women were chosen by a negative human chorionic gonadotrophin result.…”
Section: Sample Collectionmentioning
confidence: 99%
“…16 We have previously shown that biglycan and decorin transcriptionally compensate for each other during fetal membrane maturation but lose their compensatory activity in the presence of inflammation. 17 Biglycan and decorin have also been shown to be involved in the pathophysiology of preterm birth, with dysregulation of decorin occurring in fetal membranes during the second trimester. 18,19 We have shown that mice deficient in biglycan and decorin, an animal model of EDS, deliver their pups prematurely and display morphologic as well as signaling abnormalities in their fetal membranes.…”
Section: Introductionmentioning
confidence: 99%